Intra‐Industry Information Transfers and the Post‐Earnings Announcement Drift - Kovacs, Tunde (Contemporary Accounting Research, 2016)
Abstract This study examines the role of intra‐industry information transfers in the analyst forecast‐based post‐earnings announcement drift. I find that subsequent same‐industry‐peer earnings announcements influence a firm's post‐earnings announcement drift if these subsequent announcements confirm the firm's initial earnings surprise and the firm's industry exhibits ex ante positive (common effect) intra‐industry information transfers. The results suggest that underreaction to industry‐specific information contributes to analyst forecast‐based post‐earnings announcement drift.